The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
All Days 2002
DOI: 10.2118/78498-ms
|View full text |Cite
|
Sign up to set email alerts
|

Static and Dynamic Characterization of Fracture Pattern in the Upper Jurassic Reservoirs of an Offshore Abu Dhabi Field: From Well Data to Full Field Modeling

Abstract: In the oil bearing reservoirs of a mature field in the offshore Abu Dhabi, the understanding of the fracture network is essential with growing gas and water productions. Fracture characterization and modeling at the full field scale is the key to match the production profile and to optimize infill drilling. The interpretation of fracture data from image logs and cores allows defining accurately the fracture pattern in terms of orientation, typology, density and relation with lithology and fau… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 8 publications
0
8
0
Order By: Relevance
“…An illustration on a case-study involving different seismic, structural and geological attributes can be found in Gauthier et al (2002c). Other case-studies are also presented in Gauthier et al (2002a and2002b).…”
Section: Spatial Modeling Of Fracture Densitiesmentioning
confidence: 99%
See 2 more Smart Citations
“…An illustration on a case-study involving different seismic, structural and geological attributes can be found in Gauthier et al (2002c). Other case-studies are also presented in Gauthier et al (2002a and2002b).…”
Section: Spatial Modeling Of Fracture Densitiesmentioning
confidence: 99%
“…The spatial distribution of fracture densities being necessarily uncertain, a probabilistic approach should also be preferred, that relies on multivariate statistical analysis, for relating fracture density to explicative variables, and on geostatistics for addressing the spatial variability issue. Such an approach has been proposed by Gauthier et al (2002aGauthier et al ( , 2002bGauthier et al ( and 2002c where it proved efficient on different case-studies. It is the one presented later in this article.…”
Section: Spe 107525mentioning
confidence: 99%
See 1 more Smart Citation
“…They have a very long vertical extent. The south-eastern flank and the north-western flank clearly show different faulting, the former being more faulted than the later [2] . The present day insitu stress field in the entire area is still under the influence of Zagros orogeny [3] .…”
Section: Reservoir Geology and Well Locationsmentioning
confidence: 99%
“…To model the full field fracture distribution in 3D, methods have been developed that are based on multivariate correlations between discrete fracture properties (e.g., fracture frequency) and other largescale continuous variables available from seismic data, geomechanical modeling, or other reservoir model properties (Gauthier et al, 2000;Gauthier et al, 2002a;Maerten and Maerten, 2006). These methods do, however, implicitly assume that smallscale well fracture data are hard data that should be honored and that they are implicitly geologically related to large-scale fracture or deformation systems, which is not always the case (Lamarche et al, 2012).…”
Section: A C K N O W L E D G E M E N T Smentioning
confidence: 99%